Jürgen Habermas and the Failure of Peruvian Modernity - Orozco C., Richard Antonio (2018)
In this paper the author seeks to explain why modern life in Peru is chaotic. To this purpose, the author makes use of the concept of communicative action introduced by Habermas. The author finds that modernity in Peru has failed due to the scarcity of the sort of action that seeks understanding. Instead, modernity in Peru develops through actions that seek to impose themselves, and that constitutes a regression towards a primitive and non-modern action.